His All-Holiness Ecumenical Patriarch Bartholomew І on the spiritual imperatives of orthodox theology - Предко, О.; Шашкова, Л. (Київський національний університет імені Тараса Шевченка, 2022)
The article notes that spirituality in Orthodoxy is understood actively, as spiritual life, as the experience of the church community. Moreover, the theological concept of spirituality of Bartholomew I unfolds on the following levels: etymological (spirituality is directly related to breathing, with the quality of a person, without which its existence is impossible); life-meaningful (contextual meanings, in which the process of combining the history of the concept with the history of discourse, their comprehension and rethinking in the transcendent dimension is traced); practical-spiritual (spiritual and preaching activity, the process of moral teaching, the organization of life in accordance with the "Christian science of life"). The relationship between spirituality and personality is emphasized (its components are mystery, freedom, relationship, integrity). Priority in the structural hierarchy of spirituality is the moral and ethical principle, which acts as an indicator. It determines the fullness of social and individual existence since morality is one of the main mechanisms not only for regulating relations but also for the "spiritualization" of a person, on which depends his existential experience. Attention is paid to religious practices, in particular prayer, its spiritual connotations. In the state of prayer, a person tries to build his "Self" to the level of the Other, but at the same time to remain himself. If in this goal-setting process he ceases to hear a response addressed to his unique self, in this case, the prayer loses its dialogical nature. It is emphasized that, according to Ecumenical Patriarch Bartholomew І, spirituality, firstly, acts as a way of God's activity; secondly, it is closely related to the level of development of mental life, of a certain culture of feelings; thirdly, spirituality is recognized as a value that is the property of spiritual freedom, in which the human, the individually unique is combined with the divine, the universal; fourthly, it is the crystallization of the ethical-value core and anthropological-communicative meaning of certain religious practices; fifthly, the "code of spirituality" permeates all spheres of human existence, in which a person is affirmed both existentially and individually.

З'ясовано, що духовність у православ'ї розуміють діяльнісно, як духовне життя, як досвід церковної спільноти. Причому богословська концепція духовності Патріарха Варфоломія І розгортається на таких рівнях: етимологічний (духовність безпосередньо пов'язана з диханням, з тією якістю людини, без якої неможлива її буттєвість); сенсо-життєвий (контекстуальні смисли, у яких відстежується процес поєднання історії поняття з історією дискурсу, їхнє осмислення та переосмислення у трансцендентному вимірі); практично-духівничий (духовно-проповідницька діяльність, процес морального учіння, організація життя відповідно до "християнської науки життя"). Підкреслено взаємозв'язок духовності й особистості (її складовими є тайна, свобода, стосунок, цілісність). Пріоритетним у структурній ієрархії духовності є моральнісно-етичне начало, яке постає як індикатор, що визначає наповненість соціального й індивідуального буття, оскільки мораль є одним з головних механізмів не тільки регулювання відносин, а й "одухотворення" людини, від якого залежить її певний екзистенційний досвід. Звернено увагу на релігійні практики, зокрема й молитву, її духовні конотації. У стані молитви людина намагається вписати, убудувати себе в неї, добудувати своє "Я" до рівня Іншого, але водночас залишитися собою. Якщо в цьому цілепокладальному процесі вона перестає чути відгук, звернений до її неповторної самості – у цьому випадку молитва втрачає свою діалогічність. Закцентовано, що, за Вселенським Патріархом Варфоломієм, духовність, по-перше, є способом дієвості Бога; по-друге, вона тісно пов'язана з рівнем розвитку душевного життя, культури почуттів; по-третє, духовність визнано цінністтю, що є надбанням духовної свободи, у якій поєднується людське, індивідуально-неповторне з божественним, універсально-загальним; по-четверте, вона є кристалізацією етико-ціннісного ядра й антропологічно-комунікативного смислу тих чи інших релігійних практик; по-п'яте, код духовності пронизує всі сфери людської буттєвості, у яких людина стверджується як екзистенційно, так і персонально.
Його Всесвятість Патріарх Варфоломій І про духовні імперативи православного богослов'я
Keywords: Ecumenical Patriarch Bartholomew I; spirituality; personality; freedom; spiritual experience; Absolute; prayer; Патріарх Варфоломій І; духовність; особистість; свобода; духовний досвід; Абсолют; молитва